Upper gastrointestinal endoscopy in children: The Lagos University Teaching Hospital experience - Oluwafunmilayo Funke Adeniyi; Olufunmi A Lesi; Emuobor A Odeghe; Oyebola Adekola; Abiola Oduwole (South African Medical Association, 2016)
Background. Paediatric endoscopy is now standard care in the developed world for the management of gastrointestinal (GI) disorders. However, in developing countries endoscopy remains an underutilised tool. Objective. To determine the indications and the spectrum of endoscopic findings in children seen at the Lagos University Teaching Hospital, Nigeria. Methods. The indications for upper GI endoscopy and endoscopic findings in children ≤16 years old, referred for the procedure from June 2013 to June 2016, were documented. The endoscopic yield in these children was also determined. Results. In total 71 children were referred for upper GI endoscopy during the study period. There were 35 boys and 36 girls aged 3 months to 16 years. The indications for upper endoscopy were recurrent abdominal pain in 37 (52.1%), upper GI bleeding in 17 (23.9%), recurrent vomiting in 7 (9.9%), dyspepsia in 5 (7.0), heartburn in 2 (2.8%), dysphagia in 1 (1.4), portal hypertension in 1 (1.4) and ingestion of corrosives in 1 (1.4%) of the subjects. Endoscopic findings were as follows: gastritis 19 (26.8%), hiatus hernia in 13 (18.3%), gastric erosions in 12 (16.9%), oesophageal varices 6 (8.4%), duodenitis in 4 (5.6%), gastric ulcer in 3 (4.2%), gastric polyp in 2 (2.8%). The overall endoscopic yield was 60.2%. Conclusion. There is a need to increase the awareness of the role of paediatric endoscopy in the diagnosis and treatment of GI disorders in developing countries. Recurrent abdominal pain still remains a relevant indication for the procedure. The need to develop training programmes for paediatric endoscopy and paediatric gastroenterology in general in developing countries cannot be overemphasised.